The Influence of Sarcasm on Social Media: The Dilemma of Eroding Manners and Politeness in Language among Gen Z - Dewi Anggraini; Nurulanningsih Nurulanningsih (PT FORMOSA CENDEKIA GLOBAL, 2026)
The advancement of digital technology and social media has significantly changed communication patterns, especially among Generation Z. As digital natives, they are accustomed to using sarcasm in online communication, which contributes to the erosion of politeness and language etiquette. This study adopts a qualitative descriptive approach using a literature review method. Data were collected from various journals, articles, and academic sources discussing the use of sarcasm by Gen Z on social media. The findings indicate that sarcasm is frequently used to express criticism, mockery, and disapproval, particularly toward public figures. However, uncontrolled sarcasm often leads to negative impacts such as hate speech, body shaming, and cynical comments that are increasingly normalized. This phenomenon reflects a shift in communication values. Therefore, strengthening digital literacy and language ethics education in families, schools, and social media platforms is essential to foster a healthy, respectful, and civilized digital communication environment.